Titanium alloy material with good biocompatibility and preparation method thereof
By roughening the surface of the titanium alloy matrix, covering porous ceramic materials and assembling the composite molecular layer, the problem of coating peeling after titanium alloy implantation is solved, and its biocompatibility and stability is significantly improved, and it is suitable for medical implants.
Patent Information
- Application Number
- CN202411567156.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-03-11
AI Technical Summary
After titanium alloy is implanted into the human body, corrosion and friction are prone to occur during long-term use, resulting in the coating falling off, reducing the service life of titanium alloy, and how to improve the biocompatibility of titanium alloy materials to enhance connection with the human body is a key issue.
The biocompatibility of the titanium alloy material is improved by roughening the surface of the titanium alloy matrix, coating the porous ceramic material, and assembling a composite molecular layer, including fibronectin and amino acids, on its surface.
The biocompatibility of titanium alloy materials is significantly improved, making it more suitable for medical implants, enhances the binding with bone tissue, and improves the stability and long-term use effect of the implant.
Smart Images

Figure BDA0005119546790000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of titanium alloys, and in particular to a titanium alloy material with good biocompatibility and a preparation method thereof. Background Art
[0002] Titanium alloys are widely used in surgical implants, mainly due to their excellent biocompatibility, excellent mechanical properties and low density. These properties make titanium alloys the material of choice for medical implants, especially in the fields of orthopedics and dentistry. Because titanium alloys are chemically very stable, they do not react adversely with the biological environment in the body. This makes them non-allergic or rejection-prone and suitable for long-term implantation in the body. Titanium alloys can form a strong bond with bones in bone tissue and promote bone healing and regeneration. Therefore, titanium alloys are often used in applications such as fracture fixation, bone reconstruction and artificial joints.
[0003] However, in actual application, titanium alloys are often surface treated, such as coating with a layer of ceramic material to improve their antibacterial effect. However, as titanium alloys are implanted in the human body, they are inevitably accompanied by corrosion and friction during long-term use, which can easily cause the coating to fall off and reduce the service life of the titanium alloy. Therefore, how to improve the biocompatibility of the alloy material and make the connection between the titanium alloy material and the human body closer is one of the key concerns in this field. Summary of the invention
[0004] In order to solve at least one of the above problems, the present invention provides a method for preparing a titanium alloy material with good biocompatibility, comprising the following steps:
[0005] S10: obtaining a titanium alloy substrate, and performing surface roughening treatment on the titanium alloy substrate to obtain alloy A;
[0006] S20: coating the surface of alloy A with a porous ceramic material to obtain alloy B;
[0007] S30: assembling a composite molecular layer on the surface of alloy B to obtain a titanium alloy material;
[0008] The composite molecular layer includes a first biomolecule and a second biomolecule; the first biomolecule is fibronectin; and the second biomolecule is amino acid.
[0009] In this technical solution, the surface of the titanium alloy substrate is first roughened to increase the surface area and adhesion, laying the foundation for subsequent processing steps. Then, a porous ceramic material is coated on the roughened titanium alloy surface. This porous structure can promote bone bonding and tissue growth, while improving the biocompatibility of the material. Finally, a composite molecular layer is assembled on the surface of the ceramic coating layer, including fibronectin and amino acids. These biomolecules can further promote cell attachment, proliferation and tissue regeneration. The combination of the porous ceramic and composite molecular layer of the titanium alloy material thus obtained can significantly improve the biocompatibility of the titanium alloy material, making it more suitable for use as a medical implant; on the other hand, the porous structure helps to closely integrate with bone tissue, improve the stability of the implant and the long-term use effect; the composite molecular layer of fibronectin and amino acids can stimulate cell growth and tissue repair, and accelerate the integration process of the implant in the body.
[0010] Furthermore, in step S10, the surface roughening treatment is sandblasting, wherein the working pressure of the sandblasting is 0.4-0.8 MPa, the sandblasting distance is 10-30 cm, and the sandblasting time is 30-50 s.
[0011] In this technical solution, sandblasting is a common surface roughening technology. The surface of titanium alloy is mechanically polished by high-speed jetting of abrasive particles, thereby increasing its surface roughness and surface area. This treatment helps to improve the adhesion of the material and the bonding strength of the subsequent treatment layer. Among them, the pressure range is set between 0.4 and 0.8MPa to ensure that the sandblasting particles can effectively impact and polish the surface of the titanium alloy without excessively damaging the material; the sandblasting distance is set to 10 to 30 cm to ensure that the sandblasting particles can evenly cover the surface of the titanium alloy, while avoiding surface damage caused by too close a distance or poor treatment effect caused by too far a distance; the sandblasting time is set to 30 to 50 seconds to ensure that the surface roughness reaches the expected level and does not cause excessive wear to the titanium alloy substrate. By controlling the pressure, distance and time of sandblasting, this solution can obtain a uniform and controllable surface roughness, which is crucial for subsequent porous ceramic coating and composite molecular layer assembly. Optimized sandblasting can improve the adhesion of the titanium alloy surface, help the firm bonding of porous ceramic materials, and thus improve the stability and service life of the overall material. Uniform surface roughening helps improve the biocompatibility of titanium alloy materials, enabling them to better integrate with biological tissues in medical applications and promote cell growth and tissue repair.
[0012] Further, step S20 includes: dispersing palladium chloride, silicon powder and calcium dihydrogen phosphate in an organic solvent to prepare a coating, spraying the coating on the surface of alloy A through an atomizer, and scanning the surface of alloy A using a femtosecond laser heat source under a protective atmosphere to obtain alloy B.
[0013] In this technical solution, a uniform porous ceramic layer can be obtained by precisely controlling the spraying and laser processing, which helps to improve the overall performance and biocompatibility of the material. Among them, femtosecond laser processing can firmly fix the ceramic layer to ensure that it will not fall off during use, thereby improving the adhesion between the titanium alloy and the ceramic layer; the high precision and low thermal diffusion characteristics of the femtosecond laser reduce the thermal damage to the matrix material, ensuring that the performance of the titanium alloy matrix will not be negatively affected. Calcium dihydrogen phosphate, as the matrix of the ceramic material, forms a porous material under the action of laser femtosecond. At the same time, because it can be well combined with bone tissue, it promotes bone healing and regeneration; thereby improving biocompatibility. Silicon powder can form a hard phase with the titanium alloy matrix, such as Ti5Si3 or TiSi2, thereby improving the hardness and wear resistance of the titanium alloy.
[0014] Furthermore, in the coating, the ratio of palladium chloride, silicon micropowder and calcium dihydrogen phosphate is 1:(2-3):(5-10) by mass; each 1g of palladium chloride corresponds to 2-3L of organic solvent; the protective atmosphere includes nitrogen and argon, wherein the flow ratio of nitrogen and argon is 10-15:100.
[0015] In this technical solution, the specific molar ratio of palladium chloride, silicon micropowder and calcium dihydrogen phosphate can ensure the best effect of the material during the spraying process, forming a porous ceramic layer with uniform performance and stable structure. The ratio of 20-30 liters of organic solvent for every 1 mol of palladium chloride ensures the uniformity of the spraying process and avoids the problems of particle precipitation or uneven coating. The flow ratio of nitrogen and argon ensures the stability of the protective atmosphere, effectively prevents the negative impact of reactive gases on the sprayed layer and the titanium alloy surface, and ensures the quality of laser processing. The optimized protective atmosphere and material ratio help to improve the quality and adhesion of the sprayed layer, reduce thermal damage, and enhance the performance of the final product, including wear resistance, biocompatibility, etc. Preferably, the spraying amount of the ceramic layer is determined according to the surface area of alloy A, and every 1m 2 Spray 0.05-0.1L of paint on the surface area.
[0016] Furthermore, the pulse energy of the femtosecond laser is 20-100 μJ; the pulse repetition frequency is 60-80 kHz.
[0017] In this technical solution, the regulation of pulse energy enables the laser to precisely control the heat input, thereby achieving efficient sintering of the ceramic layer, avoiding overheating or insufficient sintering problems, and ensuring the uniformity and stability of the ceramic layer. High repetition rate laser pulses help speed up surface treatment, reduce processing time, and improve the consistency and accuracy of the treatment.
[0018] Further, step S30 includes:
[0019] S31: Activate alloy B.
[0020] S32: dissolving the first biomolecule and the second biomolecule in a buffer to obtain a composite solution;
[0021] S33: Cooling the activated alloy B to room temperature, immersing it in a composite solution, controlling the temperature of the composite solution to be 35-45° C., and reacting for 4-6 hours to obtain a titanium alloy material.
[0022] In this technical solution, the first biomolecule is fibronectin, which can be used to promote cell proliferation and tissue repair; amino acids can provide the nutrients required for cell growth and repair; the buffer is used to adjust the pH value of the solution to ensure that fibronectin and amino acids remain active in a stable environment. The preparation of the composite solution ensures that fibronectin and amino acids can be effectively dissolved and act on the surface of alloy B at an appropriate concentration and stability. Through the functionalization of fibronectin and amino acids, the biocompatibility of alloy B can be significantly improved, making it suitable for use in the biomedical field, such as bone implants or other medical devices.
[0023] Furthermore, in step S31, the activation treatment is: heat treating the alloy B at a temperature of 200-450° C. for 2-3 hours.
[0024] In this technical solution, the palladium on the surface of alloy B can be activated by heat treatment at a certain temperature. The activated palladium is easy to cooperate with amino acids, thereby cross-linking the amino acids to the surface of alloy B more tightly.
[0025] Furthermore, the amino acid includes at least one of lysine and valine.
[0026] The present invention also provides a titanium alloy material with good biocompatibility, which is prepared by any of the above methods.
[0027] The present invention also provides an implant with good biocompatibility, which is prepared by using the titanium alloy material. DETAILED DESCRIPTION
[0028] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] The present invention provides a method for preparing a titanium alloy material with good biocompatibility, comprising the following steps:
[0030] S10: obtaining a titanium alloy substrate, and performing sandblasting on the titanium alloy substrate, wherein the working pressure of the sandblasting is 0.4-0.8 MPa, the sandblasting distance is 10-30 cm, and the sandblasting time is 30-50 s; obtaining alloy A.
[0031] S20: palladium chloride, silicon micropowder and calcium dihydrogen phosphate are dispersed in an organic solvent to prepare a coating, the coating is sprayed onto the surface of alloy A through an atomizer, and the surface of alloy A is scanned using a femtosecond laser heat source under a protective atmosphere to obtain alloy B.
[0032] According to the mass ratio, the ratio of palladium chloride, silicon powder and calcium dihydrogen phosphate in the coating is 1: (2-3): (5-10); 1g of palladium chloride corresponds to 2-3L of organic solvent; the protective atmosphere includes nitrogen and argon, and the flow ratio of nitrogen and argon is (10-15): 100. The pulse energy of the femtosecond laser is 20-100μJ; the pulse repetition frequency is 60-80kHz. Preferably, the spraying amount of the ceramic layer is determined according to the surface area of the alloy A, and the spraying amount of the ceramic layer is 10 ... 2 Spray 0.05-0.1L of paint on the surface area.
[0033] Specifically, palladium chloride, silicon micropowder and calcium dihydrogen phosphate are dispersed in an organic solvent, and the organic solvent is preferably a volatile substance, such as ethanol, acetone, cyclohexane, etc. Then, it is sprayed on the surface of alloy A through an atomizer, and then scanned using a femtosecond laser heat source under the condition of a protective atmosphere. A certain amount of nitrogen is introduced into the protective atmosphere, so that the silicon micropowder can generate a part of silicon nitride as a reinforcing phase under the action of the femtosecond laser, thereby improving the wear resistance of the material.
[0034] In this embodiment, a layer of porous ceramic structure is generated in situ on the surface of alloy A by femtosecond laser, in which calcium dihydrogen phosphate provides the matrix of the porous structure; silicon micropowder, silicon nitride and palladium are embedded in the interior of the porous structure. Silicon micropowder can form a hard phase with the titanium alloy matrix, such as Ti5Si3 or TiSi2, thereby improving the hardness and wear resistance of the titanium alloy. In a specific embodiment, the content of palladium chloride is controlled to be very low, and it is attached to the interior of the porous ceramic material in the form of metal palladium through the action of femtosecond laser; the role of palladium is to provide a positioning point to facilitate the assembly of the composite molecular layer.
[0035] S30: Assembling a composite molecular layer on the surface of alloy B; specifically comprising:
[0036] S31: Alloy B is heat treated at a temperature of 200-450° C. for 2-3 h.
[0037] S32: Dissolving the first biomolecule and the second biomolecule in a buffer solution to obtain a composite solution.
[0038] S33: Cooling the activated alloy B to room temperature, immersing it in a composite solution, controlling the temperature of the composite solution to be 35-45° C., and reacting for 4-6 hours to obtain a titanium alloy material.
[0039] In this embodiment, alloy B is first heat-treated to activate the palladium therein, and further assembles the first biomolecule and the second biomolecule, wherein the first biomolecule is fibronectin; the second biomolecule is an amino acid. The amino acid can be cross-linked with palladium as a ligand; preferably, the amino acid includes at least one of lysine and valine. Fibronectin can cross-link with amino acids to form a stable covalent bond. The surface of the titanium alloy material thus obtained is grafted with a composite molecular layer containing amino acids and fibronectin. The buffer solution is, for example, PBS buffer; the mass ratio of the first biomolecule, the second biomolecule, the buffer solution and the alloy B is preferably (20-30): (10-15): 100: (120-150).
[0040] The present invention also provides a titanium alloy material with good biocompatibility, which is prepared by any of the above methods. The titanium alloy material includes a three-layer structure, which is a titanium alloy matrix layer, a porous ceramic layer and a composite molecular layer from the inside to the outside. The biocompatibility of the titanium alloy is significantly improved by dual-phase modification.
[0041] The present invention also provides an implant with good biocompatibility, which is prepared by using the titanium alloy material.
[0042] Example 1
[0043] This embodiment provides a method for preparing a titanium alloy material with good biocompatibility, comprising the following steps:
[0044] S10: obtaining a titanium alloy substrate, and performing sandblasting on the titanium alloy substrate, wherein the working pressure of the sandblasting is 0.4 MPa, the sandblasting distance is 10 cm, and the sandblasting time is 30 s; obtaining alloy A. S20: dispersing palladium chloride, silicon micropowder, and calcium dihydrogen phosphate in acetone to prepare a coating, spraying it on the surface of alloy A through an atomizer, and scanning the surface of alloy A using a femtosecond laser heat source under a protective atmosphere to obtain alloy B.
[0045] According to the mass ratio, the ratio of palladium chloride, silicon powder and calcium dihydrogen phosphate is 1:2:5; 1g of palladium chloride corresponds to 2L of acetone; the protective atmosphere includes nitrogen and argon, and the flow ratio of nitrogen and argon is 10:100. The pulse energy of the femtosecond laser is 20μJ; the pulse repetition frequency is 60kHz. The spraying amount of the ceramic layer is determined according to the surface area of alloy A, and the spraying amount of the ceramic layer is 10 ... 2 Spray 0.05L of organic solvent on the surface area.
[0046] S30: Assembling a composite molecular layer on the surface of alloy B; specifically comprising:
[0047] S31: Alloy B is heat treated at 200°C for 2h.
[0048] S32: Dissolve fibronectin and lysine in PBS buffer to obtain a complex solution.
[0049] S33: cooling the activated alloy B to room temperature, immersing it in the composite solution, controlling the temperature of the composite solution to 35° C., and reacting for 4 hours to obtain a titanium alloy material, wherein the mass ratio of fibronectin, lysine, PBS buffer and alloy B is 20:10:100:120.
[0050] Example 2
[0051] This embodiment provides a method for preparing a titanium alloy material with good biocompatibility, comprising the following steps:
[0052] S10: obtaining a titanium alloy substrate, and performing sandblasting on the titanium alloy substrate, wherein the working pressure of the sandblasting is 0.8 MPa, the sandblasting distance is 30 cm, and the sandblasting time is 50 s; obtaining alloy A.
[0053] S20: palladium chloride, silicon micropowder and calcium dihydrogen phosphate are dispersed in cyclohexane to prepare a coating, which is sprayed on the surface of alloy A through an atomizer. Under a protective atmosphere, a femtosecond laser heat source is used to scan the surface of alloy A to obtain alloy B.
[0054] Among them, according to the mass ratio, the ratio of palladium chloride, silicon powder, and calcium dihydrogen phosphate is 1:3:10; 1g of palladium chloride corresponds to 3L of cyclohexane; the protective atmosphere includes nitrogen and argon, and the flow ratio of nitrogen and argon is 15:100. The pulse energy of the femtosecond laser is 100μJ; the pulse repetition frequency is 80kHz. The spraying amount of the ceramic layer is determined according to the surface area of alloy A, and every 1m 2 Spray 0.1L of paint on the surface area.
[0055] S30: Assembling a composite molecular layer on the surface of alloy B; specifically comprising:
[0056] S31: Alloy B is heat treated at 450° C. for 3 h.
[0057] S32: Dissolve fibronectin and valine in PBS buffer to obtain a complex solution.
[0058] S33: cooling the activated alloy B to room temperature, immersing it in the composite solution, controlling the temperature of the composite solution to 45° C., and reacting for 6 hours to obtain a titanium alloy material, wherein the mass ratio of fibronectin, valine, PBS buffer and alloy B is 30:15:100:150.
[0059] Example 3
[0060] This embodiment provides a method for preparing a titanium alloy material with good biocompatibility, comprising the following steps:
[0061] S10: obtaining a titanium alloy substrate, and performing sandblasting on the titanium alloy substrate, wherein the working pressure of the sandblasting is 0.7 MPa, the sandblasting distance is 20 cm, and the sandblasting time is 40 s; obtaining alloy A.
[0062] S20: palladium chloride, silicon micropowder and calcium dihydrogen phosphate are dispersed in acetone to prepare a coating, which is sprayed on the surface of alloy A through an atomizer. Under the condition of a protective atmosphere, a femtosecond laser heat source is used to scan the surface of alloy A to obtain alloy B.
[0063] According to the mass ratio, the ratio of palladium chloride, silicon powder and calcium dihydrogen phosphate is 1:2:6; 1g of palladium chloride corresponds to 2L of acetone; the protective atmosphere includes nitrogen and argon, and the flow ratio of nitrogen and argon is 12:100. The pulse energy of the femtosecond laser is 60μJ; the pulse repetition frequency is 70kHz. The spraying amount of the ceramic layer is determined according to the surface area of alloy A, and the spraying amount of the ceramic layer is 10 ... 2 Spray 0.08L of paint on the surface area.
[0064] S30: Assembling a composite molecular layer on the surface of alloy B; specifically comprising:
[0065] S31: Alloy B was heat treated at 320°C for 2.5h.
[0066] S32: Dissolve fibronectin and lysine in PBS buffer to obtain a complex solution.
[0067] S33: cooling the activated alloy B to room temperature, immersing it in the composite solution, controlling the temperature of the composite solution to 44° C., and reacting for 5 hours to obtain a titanium alloy material, wherein the mass ratio of fibronectin, lysine, PBS buffer and alloy B is 25:15:100:130.
[0068] Example 4
[0069] This embodiment provides a method for preparing a titanium alloy material with good biocompatibility, comprising the following steps:
[0070] S10: obtaining a titanium alloy substrate, and performing sandblasting on the titanium alloy substrate, wherein the working pressure of the sandblasting is 0.4 MPa, the sandblasting distance is 10 cm, and the sandblasting time is 30 s; obtaining alloy A.
[0071] S20: palladium chloride, silicon micropowder and calcium dihydrogen phosphate are dispersed in ethanol to prepare a coating, which is sprayed on the surface of alloy A through an atomizer. Under a protective atmosphere, a femtosecond laser heat source is used to scan the surface of alloy A to obtain alloy B.
[0072] Among them, according to the mass ratio, the ratio of palladium chloride, silicon powder, and calcium dihydrogen phosphate is 1:2:8; 1g of palladium chloride corresponds to 3L of ethanol; the protective atmosphere includes nitrogen and argon, and the flow ratio of nitrogen and argon is 10:100. The pulse energy of the femtosecond laser is 20μJ; the pulse repetition frequency is 60kHz. The spraying amount of the ceramic layer is determined according to the surface area of alloy A, and every 1m 2 Spray 0.06L of paint on the surface area.
[0073] S30: Assembling a composite molecular layer on the surface of alloy B; specifically comprising:
[0074] S31: Alloy B is heat treated at 250° C. for 2 h.
[0075] S32: Dissolve fibronectin and lysine in PBS buffer to obtain a complex solution.
[0076] S33: cooling the activated alloy B to room temperature, immersing it in the composite solution, controlling the temperature of the composite solution to 36° C., and reacting for 4 hours to obtain a titanium alloy material, wherein the mass ratio of fibronectin, lysine, PBS buffer and alloy B is 25:12:100:125.
[0077] Example 5
[0078] This embodiment provides a method for preparing a titanium alloy material with good biocompatibility, comprising the following steps:
[0079] S10: obtaining a titanium alloy substrate, and performing sandblasting on the titanium alloy substrate, wherein the working pressure of the sandblasting is 0.8 MPa, the sandblasting distance is 20 cm, and the sandblasting time is 50 s; obtaining alloy A.
[0080] S20: palladium chloride, silicon micropowder and calcium dihydrogen phosphate are dispersed in cyclohexane to prepare a coating, which is sprayed on the surface of alloy A through an atomizer. Under a protective atmosphere, a femtosecond laser heat source is used to scan the surface of alloy A to obtain alloy B.
[0081] Among them, according to the mass ratio, the ratio of palladium chloride, silicon powder, and calcium dihydrogen phosphate is 1:3:7; 1g of palladium chloride corresponds to 3L of cyclohexane; the protective atmosphere includes nitrogen and argon, and the flow ratio of nitrogen and argon is 15:100. The pulse energy of the femtosecond laser is 100μJ; the pulse repetition frequency is 80kHz. The spraying amount of the ceramic layer is determined according to the surface area of alloy A, and every 1m 2Spray 0.1L of paint on the surface area.
[0082] S30: Assembling a composite molecular layer on the surface of alloy B; specifically comprising:
[0083] S31: Alloy B is heat treated at 420° C. for 3 h.
[0084] S32: Dissolve fibronectin and lysine in PBS buffer to obtain a complex solution.
[0085] S33: cooling the activated alloy B to room temperature, immersing it in the composite solution, controlling the temperature of the composite solution to 43° C., and reacting for 5 hours to obtain a titanium alloy material, wherein the mass ratio of fibronectin, lysine, PBS buffer and alloy B is 28:12:100:130.
[0086] Comparative Example 1
[0087] This comparative example provides a titanium alloy material, and its preparation process is similar to that of Example 1, except that palladium chloride is not used in step S20.
[0088] Comparative Example 2
[0089] This comparative example provides a titanium alloy material, and its preparation process is similar to that of Example 1, except that the protective atmosphere in step S20 does not contain nitrogen.
[0090] Comparative Example 3
[0091] This comparative example provides a titanium alloy material, and its preparation process is similar to that of Example 1, except that silicon powder is not added in step S20.
[0092] Comparative Example 4
[0093] This comparative example provides a titanium alloy material, and its preparation process is similar to that of Example 1, except that the operation of step S30 is not performed.
[0094] The titanium alloy materials obtained in Examples 1-5 and Comparative Examples 1-4 were tested. The data are as follows:
[0095]
[0096] Among them, strength and hardness reflect the mechanical properties of the alloy, and the higher the hardness, the higher the wear resistance. The contact angle can reflect the hydrophilicity or hydrophobicity of the titanium alloy surface; a smaller contact angle usually indicates a higher hydrophilicity of the material surface, which helps to improve cell attachment and growth, so the smaller the contact angle, the better the biocompatibility of the material. As can be seen from the above table, the titanium alloy material provided by the present invention significantly improves the biocompatibility of the titanium alloy through dual-phase modification.
[0097] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a titanium alloy material with good biocompatibility, characterized in that: The following steps are involved: S10: obtaining a titanium alloy substrate, and performing surface roughening treatment on the titanium alloy substrate; Alloy A is obtained; S20: coating the surface of the alloy A with a porous ceramic material; Alloy B is obtained; S30: assembling a composite molecular layer on the surface of the alloy B; Obtaining the titanium alloy material; Wherein, the composite molecular layer includes a first biomolecule and a second biomolecule; the first biomolecule is fibronectin; and the second biomolecule is an amino acid.
2. The preparation method according to claim 1, characterized in that: In step S10, the surface roughening treatment is sandblasting. The working pressure of the sandblasting treatment is 0.4-0.8 MPa, the sandblasting distance is 10-30 cm, and the sandblasting time is 30-50 s.
3. The preparation method according to claim 1, characterized in that: Step S20 includes: Palladium chloride, silicon micropowder and calcium dihydrogen phosphate are dispersed in an organic solvent to prepare a coating, and the coating is sprayed on the surface of the alloy A through an atomizer. Under the condition of protective atmosphere, a femtosecond laser heat source is used to scan the surface of the alloy A to obtain alloy B.
4. The preparation method according to claim 3, characterized in that: In the coating, the mass ratio of palladium chloride, silicon powder and calcium dihydrogen phosphate is: 1: (2-3): (5-10); wherein 1g of palladium chloride corresponds to 2-3L of organic solvent; The protective atmosphere includes nitrogen and argon, wherein the flow ratio of nitrogen to argon is (10-15):
100.
5. The preparation method according to claim 3, characterized in that: The pulse energy of the femtosecond laser is 20-100 μJ, and the pulse repetition frequency is 60-80 kHz.
6. The preparation method according to claim 1, characterized in that: Step S30 includes: S31: activating the alloy B. S32: dissolving the first biomolecule and the second biomolecule in a buffer to obtain a composite solution; S33: Cooling the activated alloy B to room temperature, immersing it in the composite solution, controlling the temperature of the composite solution to be 35-45° C., and reacting for 4-6 hours to obtain the titanium alloy material.
7. The preparation method according to claim 6, characterized in that: In step S31, the activation treatment is: heat treating the alloy B at a temperature of 200-450° C. for 2-3 hours.
8. The preparation method according to claim 6, characterized in that: The amino acid includes at least one of lysine and valine.
9. A titanium alloy material with good biocompatibility, characterized in that: It is prepared by the method according to any one of claims 1 to 8.
10. An implant with good biocompatibility, characterized in that: It is prepared using the titanium alloy material as claimed in claim 9.